Pengaruh pupuk N Bio-organomineral terhadap pH, NO3-, C-organik, Na-dd, kandungan Pb tanah dan serapan Pb padi (Oryza sativa L.) pada sawah tercemar limbah tekstil - Sudirja, Rija; Masruri, Muhammad Kholil; Suryatmana, Pujawati; Rosniawaty, Santi; Kamaluddin, Nadia Nuraniya; Sandrawati, Apong (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
Lead (Pb) heavy metal pollution on rice fields in Rancaekek is caused by the disposal of textile industry waste which is not perfectly processed. The impact is a decrease in soil fertility which can threaten the food quality and agricultural sustainability. The application of N Bio-Organomineral fertilizer is one of the efforts to improve the quality of rice fields polluted with heavy metals Pb and high Na content. This research aims to find out the effect of N Bio-Organomineral fertilizer on pH, NO3-, Na, C-organic soil, solubility of soil Pb and uptake of plants Pb. The experimental design used a Randomized Block Design (RBD) with eight treatments and four replications consisting of: 0 (control); urea 250 kg/ha; and the variation in the dose of fertilizer is 250; 500; 750; 1000; 1250; 1500 kg/ha. N Bio-Organomineral fertilizer is a modification of N fertilizer based on urea, zeolite, activated charcoal and compost enriched with Bacillus subtilis with formulation 60:20:10:10. The results showed that the application of N Bio-Organomineral fertilizer could increase the NO3- and C-organic content of the soil and reduce the Na-dd and Pb uptake of plants. Treatment of 500 kg/ha N Bio-Organomineral fertilizer was the best dose in increasing the NO3- and Corganic content of the soil and reducing Na-dd and Pb uptake of plants